Transformasi Nilai-Nilai Dakwah Menjadi Strategi Brand Loyalty: Studi pada Lembaga Pendidikan Islam Berbasis Pesantren Modern - Sofia; M Hafiduddin (Advances In Education Journal, 2025)
This Study Aims To Explore How Dakwah Values Are Transformed Into Brand Loyalty Strategies In Islamic Education Institutions. Conducted At MA Sullamul Hidayah, This Research Uses A Qualitative Descriptive Approach With Data Collected Through In-Depth Interviews, Observation, And Documentation. Key Informants Include The School Principal, Vice Principal Of Public Relations, A Teacher, And A Student's Guardian. The Findings Show That Values Such As Shiddiq, Amanah, Tabligh, And Ukhuwah Are Practically Embedded In Institutional Communication And Character Education. These Values Build Emotional And Spiritual Bonds With Students And Parents, Contributing To Sustainable Brand Loyalty. The Study Introduces The Concept Of Dakwah-Based Brand Loyalty As An Innovative Model For Islamic Educational Management, Offering A Strategic Alternative That Aligns Spiritual Values With Modern Institutional Branding.